2011
DOI: 10.1007/s11934-011-0199-8
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Photoselective Vaporization of the Prostate and Sexual Function

Abstract: Although transurethral resection of the prostate remains the gold standard treatment of lower urinary tract symptoms that are refractory to medical therapy, photovaporization of the prostate (PVP) has become a popular alternative. Early PVP studies have been encouraging, but insufficient data exist regarding the effects of PVP on long-term sexual function. This article analyzes the published data and briefly reviews the literature. The studies on PVP are heterogeneous, and other than one that showed a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Standardized functional test like International Index of Erectile Function (IIEF-5) should be taken into account in any study that has as its objective to evaluate the efficacy and functional outcome in this field, but it is important to remember how hard is to assess erectile function in studies with short follow-up. These results are important for those young patients who decide to undergo these innovative techniques [21]. Other limitations are represented by (a) the paucity of data about prostate volume reduction in the studies comparing the 180 versus 120-W technologies; (b) the lack of data on patients at high risk of bleeding treated with the 180-W XPS GL; (c) the lack of specific data about the relation between anticoagulation and perioperative morbidity; (d) the significant differences existing between enucleating procedure [as holmium laser enucleation of the prostate (HoLEP), thulium laser enucleation of the prostate (TULEP) or GreenLight laser enucleation of the prostate (GreenLEP)] and the 180-W XPS pure vaporization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized functional test like International Index of Erectile Function (IIEF-5) should be taken into account in any study that has as its objective to evaluate the efficacy and functional outcome in this field, but it is important to remember how hard is to assess erectile function in studies with short follow-up. These results are important for those young patients who decide to undergo these innovative techniques [21]. Other limitations are represented by (a) the paucity of data about prostate volume reduction in the studies comparing the 180 versus 120-W technologies; (b) the lack of data on patients at high risk of bleeding treated with the 180-W XPS GL; (c) the lack of specific data about the relation between anticoagulation and perioperative morbidity; (d) the significant differences existing between enucleating procedure [as holmium laser enucleation of the prostate (HoLEP), thulium laser enucleation of the prostate (TULEP) or GreenLight laser enucleation of the prostate (GreenLEP)] and the 180-W XPS pure vaporization.…”
Section: Discussionmentioning
confidence: 99%
“…The report of the sexual function after 180-W XPS GL was poorly reported. Only four studies were taken into consideration factors such as male sexual function and ejaculation [7,9,10,15]; in the literature, there are conflicting data on the safety of photoselective vaporization of the prostate and male sexual function [21][22][23]. Standardized functional test like International Index of Erectile Function (IIEF-5) should be taken into account in any study that has as its objective to evaluate the efficacy and functional outcome in this field, but it is important to remember how hard is to assess erectile function in studies with short follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…EF improved by 3.4 to 30 points. [59] However, a French study suggested EF appeared to be maintained after PVP, [60] whereas Bruyere et al [61] indicated a significantly decreased EF after PVP. Kuntz et al [62] randomized 200 patients to HoLEP or TURP and observed similar change of EF after 1 year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…These rates are quite similar to TURP. Reported incidences of this complication are 8.3–56.0% for KTP and 67.0–73.8% for TURP …”
Section: Retrograde Ejaculationmentioning
confidence: 99%
“…Reported incidences of this complication are 8.3-56.0% for KTP and 67.0-73.8% for TURP. [32][33][34][35] Kim et al tried to overcome retrograde ejaculation by sparing the ejaculatory hood, defined as the paracollicular and supracollicular tissue longer than 1 cm proximal to the veru montanum, 36 this procedure resulting in a higher rate (92%) of antegrade ejaculation with TURP 37 and laser vaporization of the prostate. 38 For HoLEP, Kim et al found that the same technique preserved ejaculation in 46.2% of patients in their study, compared with 26.9% of those undergoing standard HoLEP.…”
Section: Retrograde Ejaculationmentioning
confidence: 99%